Tillage systems affect soil nitrogen availability and interact growth parameters of different faba bean cultivars - AHMED F. M. AL-ENEZY; BASIM A. ZAIDAN; ALI F. ALMEHEMDI; ALAA A. HUSSEIN; MUSTAFA ABED AL-JABBAR SALIH (Society for Indonesian Biodiversity, 2023)
Abstract. Al-Enezy AFM, Zaidan BA, Almehemdi AF, Hussein AA, Salih MAA. 2023. Tillage systems affect soil nitrogen availability and interact growth parameters of different faba bean cultivars. Biodiversitas 24: 5558-5564. A field trial was conducted during the winter season of 2021-2022 in one of the agricultural lands of Hamid Shaban village, which belongs to Abu Ghraib District of Baghdad Province (33°17'51.3